Ethics, Patents and Genome Editing: A Critical Assessment of Three Options of Technology Governance - Feeney, Oliver; Cockbain, Julian; Sterckx, Sigrid (Frontiers in Political Science, 2021)
Current methods of genome editing have been steadily realising the once remote possibilities of making effective and realistic genetic changes to humans, animals and plants. To underpin this, only six years passed between Charpentier and Doudna’s 2012 CRISPR-Cas9 paper and the first cases of gene-edited humans. While the traditional legislative and regulatory approach of governments and international bodies is evolving, there is still divergence, unevenness and lack of clarity. However, alongside the technical progress, innovation has also been taking place in terms of ethical guidance from the field of patenting. The rise of so-called ‘ethical licensing’ is one such innovation, where patent holders’ control over genome editing techniques creates a form of private governance over possible uses of gene-editing through ethical constraints built into their licensing agreements. While there are some immediately apparent advantages (epistemic, speed, flexibility, global reach, court enforced), this route seems problematic for three important reasons: 1) lack of democratic legitimacy/procedural justice, 2) voluntariness, wider/global coordination, and sustainability/stability challenges and 3) potential motivational effects/problems. Unless these three concerns are addressed, it is not clear if this route is an improvement on the longer, slower traditional regulatory route. Some of these concerns seem potentially addressed by another emerging patent-based approach. Parthasarathy proposes government-driven regulation using the patent system, which, she argues, has more transparency and legitimacy than the ethical licensing approach. This proposal includes the formation of an advisory committee that would guide this government-driven approach in terms of deciding when to exert control over gene editing patents. While there seem to be some apparent advantages with this approach over both traditional regulation and ethical licensing, problems also arise – such as a ‘half-way house’ of global democratic legitimacy that may not be legitimate enough whilst still compromising speed of decision-making under the ‘ethical licensing’ approach. This paper seeks to highlight the various advantages and disadvantages of the three main regulatory options – traditional regulation, ethical licensing and Parthasarathy’s approach – before suggesting an important, yet realistically achievable, amendment of TRIPS and an alternative proposal of a WTO ethics advisory committee.